Menedžersko-financijski instrumenti telekomunikacijske ekspanzije - Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
By traditional approach and financing models the national telecommunications operator’s list growth rates of typical 3% up to maximum 6% annually. Innovative/business inspected approach and bridging of the existing managerial financial ’gap’ it is possible to reach the growth rates of 7-12%. With support of telecommunication policy, more liberal regulations and structured financial infrastructure, telecommunications expansion can mark the rate in the order of 15-20%. · The countries of Eastern Europe have respective requirements and demand for expansion. Some of them take adequate steps towards the introduction of adequate legal/ political regulations and managerial/financial training of telecommunications operators for the materialization of the set-up objectives.